2007
DOI: 10.1614/ws-07-003.1
|View full text |Cite
|
Sign up to set email alerts
|

Tillage and Soybean Canopy Effects on Common Cocklebur (Xanthium strumarium) Emergence

Abstract: Field experiments were conducted in Pendleton, SC, in 2004 and 2005, to determine the influence of tillage with or without soybean on common cocklebur emergence. Treatments included no-till/no soybean (NTNS), no-till plus soybean (NTS), tillage/no soybean (TNS), and tillage plus soybean (TS). Emergence was monitored from an artificial seed bank in 2004 and a natural seed bank in 2005. Overall, common cocklebur emerged from early May through late October and presented multiple emergence. In no-till plots with o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 40 publications
0
19
0
Order By: Relevance
“…Conservation agriculture (CA) is being promoted globally as a farming system that can address many of those concerns and increase the overall economic productivity of mechanised agriculture (Norsworthy and Oleivera 2007;Hobbs et al 2008;Sanyal et al 2008). This is in direct contrast to sub Saharan Africa where CA is promoted as a potential solution to the production problems faced by small holder farming families in their quest to attain household food security (Haggblade and Tembo 2003;Mazvimavi and Twomlow 2009;Rockstrom et al 2009;Twomlow et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Conservation agriculture (CA) is being promoted globally as a farming system that can address many of those concerns and increase the overall economic productivity of mechanised agriculture (Norsworthy and Oleivera 2007;Hobbs et al 2008;Sanyal et al 2008). This is in direct contrast to sub Saharan Africa where CA is promoted as a potential solution to the production problems faced by small holder farming families in their quest to attain household food security (Haggblade and Tembo 2003;Mazvimavi and Twomlow 2009;Rockstrom et al 2009;Twomlow et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The type of weed species and weed seedling density are strongly influenced by the tillage regime implemented. Norsworthy and Oliveira () found that spring tillage increased the emergence of Xanthium strumarium L. (common cocklebur) while having little influence on Amaranthus palmeri S. Wats (Palmer amaranth). Additionally, Bullied et al .…”
Section: Introductionmentioning
confidence: 99%
“…Tillage can be very effective in reducing weed populations, as it can affect the viability of weed seeds and their subsequent distribution in the soil (Norsworthy & Oliveira, 2007). An appropriate tillage method and timing can destroy many weed seedlings early in their life cycle, thus reducing competition with crops for nutrients, light and water (Blackshaw et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Senna obtusifolia (Sicklepod) and Xanthium strumarium (common cocklebur) are two of the most important weeds species in row cropping systems of the mid-and southeastern United States (US) [1,2] as they have the potential to become major weeds of many crops, including soybean, cotton, and maize in short time periods [3]. In addition, these species can invade and dominate pastures, roadsides, fence lines, creek banks, and other disturbed areas [4].…”
Section: Introductionmentioning
confidence: 99%